2021
DOI: 10.1371/journal.pone.0257540
|View full text |Cite
|
Sign up to set email alerts
|

General population perspectives of dementia risk reduction and the implications for intervention: A systematic review and thematic synthesis of qualitative evidence

Abstract: Background Evidence for the potential prevention of dementia through lifestyle risk factor modification is growing and has prompted examination of implementation approaches. Understanding the general population’s perspectives regarding dementia risk reduction is key to implementation. This may provide useful insights into more effective and efficient ways to help people change relevant beliefs, motivations and behaviour patterns. We conducted a systematic review and thematic synthesis of qualitative evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 97 publications
(442 reference statements)
2
32
0
1
Order By: Relevance
“…This sample offers a meaningful slice of the population for the project’s public health objectives. Eligibility criteria are age 50 years or older (based on the likelihood of higher personal health motivations and to provide maximum opportunity for observing longitudinal changes from midlife in behavioral, cognitive, and biological markers [ 35 ]), resident of Tasmania, having an email address, and having access to the internet. Invitations to join the study are regularly and widely distributed using web-based, print, and broadcast media; community talks; information booths; social media; flyers; and posters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This sample offers a meaningful slice of the population for the project’s public health objectives. Eligibility criteria are age 50 years or older (based on the likelihood of higher personal health motivations and to provide maximum opportunity for observing longitudinal changes from midlife in behavioral, cognitive, and biological markers [ 35 ]), resident of Tasmania, having an email address, and having access to the internet. Invitations to join the study are regularly and widely distributed using web-based, print, and broadcast media; community talks; information booths; social media; flyers; and posters.…”
Section: Methodsmentioning
confidence: 99%
“…Emerging evidence indicates help-seeking older adults find that knowing their own risk profile information improves their understanding of how they can reduce their risk of developing dementia [ 33 ]. This is encouraging and offers support for providing personalized feedback to help increase the personal resonance of risk reduction messages and to stimulate health behavior change [ 34 , 35 ]. This knowledge, understanding that it is possible to change one’s health status, having access to the opportunity and support required to take action, and being motivated to do so are all considered to be important contributing factors for achieving effective health-related behavior change [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is beneficial from a patient perspective to know their own level of risk for dementia. Risk scores help provide feedback on the effectiveness of preventive health activities in (close to) real-time and provide a target for patients to work toward ( 49 , 50 ).…”
Section: Conceptual and Methodological Considerationsmentioning
confidence: 99%
“…Disease-modifying treatments for ADRD remain elusive [ 8 ]. Recent literature including systematic reviews showed that up to 40% of late-onset ADRD may be prevented or at least delayed by addressing modifiable risk factors (MRFs) [ 2 , 9 ]. The interaction of MRFs in incident ADRD is complex and challenging because of the long-time frames between intervention on MRFs and the occurrence of ADRD [ 9 ].…”
mentioning
confidence: 99%
“…Recent literature including systematic reviews showed that up to 40% of late-onset ADRD may be prevented or at least delayed by addressing modifiable risk factors (MRFs) [ 2 , 9 ]. The interaction of MRFs in incident ADRD is complex and challenging because of the long-time frames between intervention on MRFs and the occurrence of ADRD [ 9 ]. Because of the potential benefits of acting on MFRs, the World Health Organization (WHO) has called for immediate implementation in clinical practice of actions targeting MRFs for ADRD reduction [ 3 ].…”
mentioning
confidence: 99%